AHP and Geospatial technology-based assessment of groundwater potential zones in Natham taluk, Tamil nadu, India - Gurugnanam Balasubramaniyan; Dheiva Arul Ganesan; Bagyaraj Murugesan; Bairavi Swaminathan; Shankar Karuppannan; Karunanidhi Duraisamy (Scientific Reports)
Abstract The world’s groundwater resources are under tremendous strain due to overuse and significant climatic changes. The need for potable water for industrial, agricultural, and domestic use is increasing worldwide, necessitating an assessment of aquifer productivity and groundwater potential. Therefore, the present study aimed to evaluate groundwater potential zones (GWPZ) in Natham Taluk, Dindigul district, a hard rock area, to promote sustainable development. The GWPZ was delineated using the Analytical Hierarchy Process (AHP) in conjunction with Remote Sensing (RS) and Geographic Information Systems (GIS), which have become essential techniques for groundwater resource retrieval, monitoring, and conservation. A total of ten thematic maps of lithology, land use/land cover, lineament density, geomorphology, soil, slope, rainfall, drainage density, Topographic Wetness Index (TWI), and curvature, all layers were integrated to define Groundwater Potential Zones (GWPZs) by weighted overlay analysis using ArcGIS and Analytical Hierarchy Process (AHP). Five types of groundwater potential were found in the study region as a consequence of the classification: very good (7.61%), good (39.70%), moderate (17.70%), low (33.03%), and very low (1.95%). The groundwater potential map (GWPM) accuracy is evaluated using the area under the curve (AUC) method; an AUC value of 0.830 indicates a reliable result. This spatial study provides a vital geospatial database for strategically planning and constructing groundwater recharge structures. In addition to supporting the long-term sustainable management of groundwater resources, the delineated zones offer practical insights for improving aquifer recharge. The study also identifies possible locations for artificial recharge, especially well-suited to areas with hard rock and semi-arid conditions.